Correlação entre morfologia urbana e os cálculos de centralidade para a predição da acessibilidade em escala local. estudo de caso sobre o bairro Buritis - Lucas Duarte Costa Lima (2020)
The research stems from the investigation of how the morphology of urban networks influences the process of formation and maintenance of centralities and how to calculate the weight exercised by individual buildings and their effect on centrality calculations. To this end, exploratory research was adopted as a methodology, aiming at developing familiarity with the phenomena described and analyzed by the theories and tools developed by the Space Syntax laboratories linked to UCL (University College London) and the City Form Lab linked to the Massachusetts Institute of Technology (MIT), in order to support subsequent research with greater understanding and precision. The relationship between the functional and spatial aspects of the centralities was investigated in order to understand how this relationship is driven by social and economic life in cities. As an analysis technique, a case study was carried out on the accessibility of the Buritis neighborhood in Belo Horizonte, MG, using as sample the georeferencing of micro and small businesses registered in the neighborhood and its correlation with the centrality calculations and accessibility metrics from spatial configuration of the urban network on a local scale. A strong relationship between configuration and attraction was identified and it was concluded that, in order to understand centrality in a way that is robust enough to make predictions and guide decisions, one must try to understand it as a continuous and space-functional process not simply as a state or a series of states, at specific points in time; since considerations only about the state of centrality in public policy decisions, it means confusing a momentary state with a natural state, so that one can end up undermining the spatial dynamics that give rise to the type of centrality phenomenon that is desired conserve or revitalize. Without discarding the obvious finding that political and economic factors determine the guidelines for urban development, it was assessed that such processes actually operate only within the restrictions and limits established by the scientific finding that centrality is a spatially driven process.